Complaint management in public services: a case study at local district municipal authority in Malaysia - Saad, Shatina; Nizarwan, Muhamad Halim (2016)
This paper presents a conceptualization of the complaint management that focuses on daily customers' activities, which influencing the local municipal district authority organization’s public image. The aim of this study is to identify the major concerning areas complaints received by the local municipal district authority organization and to improve the organization’s service quality as perceived by customers. Research was conducted based on organization’s historical data, which acts as public service to all residents in one of the districts in Selangor, Malaysia.Using descriptive and Pareto Analysis, several results have emerged from the data analysis.The types of complaints were identified and classified into topmost contributors of complaints. Next, major concerning areas for topmost contributors were identified.This study has successfully determined areas which the local municipal district authority organization’s should be focusing more to minimize complaints and improving their service. Hence, suggestions were made to aid the local municipal district authority organization to counter the problem arises from the complaints itself.